243 GHz low-noise amplifier MMICs and modules based on metamorphic HEMT technology. Issue 3 (June 2014) - Berroth, Manfred; Jacob, Arne F.; Schmidt, Lorenz-Peter; Tessmann, Axel; Hurm, Volker; Leuther, Arnulf; Massler, Hermann; Weber, Rainer; Kuri, Michael; Riessle, Markus; Stulz, Hans-Peter; Zink, Martin; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Two compact H-band (220–325 GHz) low-noise millimeter-wave monolithic integrated circuit (MMIC) amplifiers have been developed, based on a grounded coplanar waveguide (GCPW) technology utilizing 50 and 35 nm metamorphic high electron mobility transistors (mHEMTs). For low-loss packaging of the circuits, a set of waveguide-to-microstrip transitions has been realized on 50-μm-thick GaAs substrates demonstrating an insertion loss of <0.5 dB at 243 GHz. By applying the 50 nm gate-length process, a four-stage cascode amplifier module achieved a small-signal gain of 30.6 dB at 243 GHz and more than 28 dB in the bandwidth from 218 to 280 GHz. A second amplifier module, based on the 35-nm mHEMT technology, demonstrated a considerably improved gain of 34.6 dB at 243 GHz and more than 32 dB between 210 and 280 GHz. At the operating frequency, the two broadband low-noise amplifier modules achieved a room temperature noise figure of 5.6 dB (50 nm) and 5.0 dB (35 nm), respectively.